(untitled) (Південний архів (історичні науки), 2022)
The article analyzes the process of formation of the Common Foreign and Security Policy of the European Union and identifies the main factors in the formation of the Common Security and Defense Policy. The development of the European Union’s global peacemaking intentions, which were aimed at creating a system of conflict prevention and prevention, is characterized. The main attention is paid to the study of the spread of the Common Security and Defense Policy to the countries of the Eastern Partnership. The purpose of the article is to study the participation of the European Union in the settlement of conflicts in the countries of the Eastern Partnership. The work uses such research methods as analysis of historical events, comparison and synthesis. The results of the study. The formation of the Common Foreign and Security Policy of the European Union took place with the aim of strengthening the foreign policy instruments of the European Union in the development of military and civilian crisis management capabilities. The introduction of the European Neighborhood Policy and the separation of its eastern direction into the “Eastern Partnership” initiative formed a new system of relations between the European Union and the countries that joined this initiative. The European Union faced the need to determine its role in conflicts on the territory of the Eastern Partnership countries. Conclusions. The formation of the Common Foreign and Security Policy of the European Union contributed to the strengthening of the institutional capacity of the European Union to take an active part in the settlement of conflicts in the Eastern Partnership region. The Eastern Partnership was aimed at achieving stability in the partner countries, however, the security component offered by the European Union did not make it possible to count on the formation of an effective counterweight to Russian encroachments on the national interests and sovereignty of the Eastern Partnership countries. In the settlement of conflicts on the territory of the Eastern Partnership countries, the European Union appears not as a political actor with a clear plan to resolve the conflict, but rather as a provider of humanitarian and financial aid to these countries. In particular, he created the Monitoring Mission in Georgia and the Advisory Mission in Ukraine. Despite certain positive results in the settlement of conflicts, the actions of the European Union could not bring peace to Eastern Europe and the South Caucasus and ensure post-conflict stabilization.